Diary of a country priest - Bernanos, Georges
In Ambricourt, an idealistic young Priest (Claude Laydu) arrives to be the local parish priest. He attempts to live a Christ-like life, but his actions are misunderstood. The community of the small town does not accept him, and although having a serious disease in the stomach, the inexperienced and frail priest tries to help the dwellers, and has a situation with the wealthy family of the location. Written by Claudio Carvalho, Rio de Janeiro, Brazil